Characterization of Cr/Bentonite and HZSM-5 Zeolite as Catalysts for Ethanol Conversion to Biogasoline - Widjaya, Robert Ronal; Soegijono, Bambang; Rinaldi, Nino (UI Scholars Hub, 2012)
The characterization on Cr/Bentonit and Zeolit HZSM-5 catalysts for ethanol catalytic process to biogasoline (equal to gasoline) has been done in this study. Cr/Bentonit has high acidity and resistant to a lot of moisture, in addition to being able to processing feed which a lot of moisture (>15%) from ethanol-water mixture, it is also not easy to deactivated. Cr/Bentonit which is then used as the catalyst material on the process of ethanol conversion to be biogasoline and the result was compared with catalyst HZSM-5 zeolite. Several characterization methods: X-ray diffraction, Brunauer Emmett Teller (BET), thermogravimetry analysis (TGA), and catalyst activity tests using catalytic Muffler instrument and gas chromatography-mass spectrometry (GC-MS) for product analysis were performed on both catalysts. From acidity measurement, it is known that acidity level of Cr/Bentonit is the highest and also from XRD result, it is known there is shift for 2theta in Cr/Bentonit, which indicates that Cr-pillar in the Bentonite can have interaction. It is also supported by BET data that shows the addition of specific surface are in Cr/Bentonite compared with natural Bentonite before pillarization. Futhermore catalyst activity test produced the results, analyzed by GC-MS, identified as butanol and also possibly formed hexanol, decane, dodecane, undecane, which are all included in gasoline range (C4 until C12).